Carcinoma of the colon and rectum with deregulation of insulin-like growth factor 2 signaling: clinical and molecular implications - Belharazem, Djeda; Sauer, Christian; Sticht, Carsten; Marx, Alexander; Hofheinz, Ralf-Dieter; Post, Stefan; Kienle, Peter (Journal of gastroenterology, 2016)
BackgroundLoss of imprinting (LOI) of the insulin-like growth factor 2 (IGF2) is an early event in the development of colorectal cancer (CRC). Whether LOI of IGF2 denotes a molecular or clinical cancer subgroup is currently unknown.MethodsTumor biopsies and paired normal mucosa from 399 patients with extensive clinical annotations were analyzed for LOI and IGF2 expression. LOI status in 140 informative cases was correlated with clinicopathologic parameters and outcome.ResultsLOI was frequent in normal mucosa and tumors and occurred throughout the large intestine. LOI was unrelated to microsatellite instability, KRAS mutation status, stage, and survival. However, CRC with LOI showed increased IGF2 protein levels and activation of AKT1. Gene expression analysis of tumors with and without LOI and knockdown of IGF2 in cell lines revealed that IGF2 induced distinct sets of activated and repressed genes, including Wnt5a, CEACAM6, IGF2BP3, KPN2A, BRCA2, and CDK1. Inhibition of AKT1 in IGF2-stimulated cells showed that the downstream effects of IGF2 on cell proliferation and gene expression were strictly AKT1-dependent.ConclusionsLOI of IGF2 is a frequent and early event in CRC that occurs both in the adenomatous polyposis coli (APC) gene-mutated and serrated route of carcinogenesis. LOI leads to overexpression of IGF2, activates IGF1R and AKT1, and is a powerful driver of cell proliferation. Moreover, our results suggest that IGF2 via AKT1 also contributes to non-canonical wnt signaling. Although LOI had no significant impact on major clinical parameters and outcome, its potential as a target for preventive and therapeutic interventions merits further investigation.
Gesehen am 01.07.2019